Urban air pollution of nitrogen oxides frem traffic - Hertel, Ole; Berkowicz, Riwin; Vignatti, Elisabetta; Palmgren, Finn (Proceedings from the Annual Transport Conference at Aalborg University, 1995)
Traffic is a major source of nitrogen oxides, especially in urban areas where the traffic density is high. Dispersion of nitrogen oxides in urban areas is governed mainly by wind conditions. In a street canyon the wind generates a vortex, which leads to considerable differences in concentration levels on the two sides of the street. Nitrogen dioxide can cause problems for people suffering from respiratory diseases, especially asthma patients are sensitive to high concentrations. The introduction of catalytic converters has decreased the nitrogen oxide concentrations, and the levels are expected to decrease further in the coming years. However, the catalytic technique is today limited to petrol driven vehicles. Since heavy vehicles, e.g. buses and trucks, contribute significantly to the NOx emission, this will limit the reduction in many urban streets. At the same time the traffic is increasing in many streets. The nitrogen oxide emission from traffic contains only 5 to 20% nitrogen dioxide, the remaining 80 to 95% is in the form of nitrogen monoxide, which is thought to be harmless. In the presence of ozone, NO is quickly chemically transformed to NO2. Due to the increasing pollution in Europe, levels of tropospheric ozone (ozone in the lower part of the atmosphere) has increased. In Danish urban streets ozone is the limiting factor for the NO2 levels. Ozone is photo-chemically produced due to emissions of NOx and hydrocarbons on a European scale. The ozone concentrations in Denmark are governed by large scale processes and can therefore only be reduced by reduction of emissions on European scale.